The Implementation of Diagnostic Assessment to Support Diafferentiated Instruction in English Learning at SMK N 1 Pringapus - WARDHANI, ARUM (English Education Journal, 2023)
The purpose of this study was to investigate the implementation diagnostic assessment to support differentiated instruction in English learning at SMK N 1 Pringapus.  It involved the teacher and 34 students in the eleventh-grade majoring in automotive academic year 2023/2024, which employed a mixed-method research design. The qualitative data analysis from teacher’ interview, classroom observation included documents such as test items from diagnostic assessments, students' outcomes, and lesson plans (modul ajar) revealed that the finding had explained how the teacher applied the sequences of the diagnostic assessment to assess students’ readiness, interest and learning profile. Moreover, the teacher was able to utilize the results of diagnostic assessments to design differentiated instruction by carrying out the process of differentiating content, processes and products. On the other hand, the paired t-test revealed a significance difference in students’ score before and after the implementation of differentiated instruction with topic explanation text. The average mean value of the pre- test was 63.79, and the post-test was 78.08. It led to the conclusion that the implementation of differentiated instruction in English class strengthen the student knowledge, understanding, and skill. This study was remarkable because it presented a novel perspective on how teacher implementing the diagnostic assessment and using the data to design and apply step by step differentiated instruction in English learning.